Systematics of Eutropis rugifera (Stoliczka, 1870) (Squamata: Scincidae) including the redescription of the holotype - Amarasinghe, A.a. Thasun; Poyarkov Jr., Nikolay A.; Campbell, Patrick D.; Leo, Sandy; Supriatna, Jatna; Hallermann, Jakob (Zootaxa, 2017)
Eutropis rugifera has long been identified as a widespread species complex distributed in Nicobar, Peninsular Malaysia, Greater Sundaic Islands, Bali, Sulawesi and the Philippines. This skink was described by Stoliczka in 1870 from Nicobar Island based on a single specimen (holotype by monotypy). Later, Peters (1871), Bartlett (1895) and Werner (1896) described three more species which were morphologically similar to Euprepes percarinatus (from Java), Mabuia rubricollis (Borneo) and M. quinquecarinata (Sumatra) respectively, which are currently considered junior objective synonyms of Eutropis rugifera. We examined all the available synonym types and voucher specimens of Eutropis rugifera deposited at several museums. A morphological examination of the types of this species and mtDNA analysis (584 bp of 16S rRNA) of the samples from different biogeographic regions revealed that Eutropis rugifera from Nicobar Island, Bali Island, and Bawean Island are composed of a monophyletic species. However, the taxonomic status of the above population requires further clarification, and the population in Bawean Island may represent a cryptic species. Finally, we provide a complete redescription of E. rugifera based on its holotype.